2011
DOI: 10.3109/02770903.2011.624235
|View full text |Cite
|
Sign up to set email alerts
|

The School Inner-City Asthma Study: Design, Methods, and Lessons Learned

Abstract: Background Children spend a significant amount of time in school. Little is known about the role of allergen exposure in school environments and asthma morbidity. Objectives The School Inner-City Asthma (SICAS) is an NIH funded prospective study evaluating the school/classroom specific risk factors and asthma morbidity among urban children Methods/Results This paper describes the design, methods, and important lessons learned from this extensive investigation. A single center is recruiting 500 elementary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 36 publications
0
96
0
Order By: Relevance
“…Phipatanakul et al (2011) and Kimmel et al (2005) emphasized the necessity of improved communication but Adgate et al (2000) were confronted with a lack of interest of the local media in press-releases about a planned survey because the media was only interested in results. Instead, Adgate et al (2000) were more successful in recruiting families by direct contact of potential participants.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Phipatanakul et al (2011) and Kimmel et al (2005) emphasized the necessity of improved communication but Adgate et al (2000) were confronted with a lack of interest of the local media in press-releases about a planned survey because the media was only interested in results. Instead, Adgate et al (2000) were more successful in recruiting families by direct contact of potential participants.…”
Section: Discussionmentioning
confidence: 96%
“…whole schools or classes) is common. Phipatanakul et al (2011) reported in their lessons learnt from the School Inner-City Asthma Study that convincing the schools was a hard job and had to be repeated every time new schools were included in the study. Therefore they concluded that efforts to engage the school staff in support of the survey have to be increased.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Study procedures were as previously described 10 and as depicted in Figure 1 . Screening questionnaires were collected each spring in participating schools to identify eligible children with asthma.…”
Section: Study Proceduresmentioning
confidence: 99%
“…Other studies have undertaken this approach successfully from a recruitment point of view but with challenges particularly related with "convincing" the schools to participate in biomedical research studies [11][12].…”
Section: Methodsmentioning
confidence: 99%